2012
DOI: 10.1080/0309877x.2012.726973
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the views of students on the use of Facebook in university teaching and learning

Abstract: Abstract:Facebook use among students is almost ubiquitous; however, its use for formal academic purposes remains contested. Through an online survey, monitoring student use of module Facebook pages and focus groups, this study explores students' current academic uses of Facebook and their views on using Facebook within university modules. Students reported using Facebook for academic purposes, notably peer-peer communication around group work and assessment; a use not always conceptualised by students as learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
2
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 20 publications
0
66
2
12
Order By: Relevance
“…Furthermore, Aydin argued that as interaction takes place in such an informal setting, students will more easily be willing to interact with their teachers otherwise, which can be especially beneficial in situations with less than desirable interaction, and that witnessing teachers being active on Facebook will more easily lead to students daring to participate and interact with said teachers, both on and "off" Facebook. Donlan (2014) has also researched students' views on Facebook-use in higher education. She reported that students in higher education are apt to participating in Facebook environments in relation to learning, not all students are willing to use Facebook in this way and that there is room to research this further, which it can be added can be of great importance given that much previous research seems to point towards an overall student satisfaction with using Facebook in connection to studies somehow.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Aydin argued that as interaction takes place in such an informal setting, students will more easily be willing to interact with their teachers otherwise, which can be especially beneficial in situations with less than desirable interaction, and that witnessing teachers being active on Facebook will more easily lead to students daring to participate and interact with said teachers, both on and "off" Facebook. Donlan (2014) has also researched students' views on Facebook-use in higher education. She reported that students in higher education are apt to participating in Facebook environments in relation to learning, not all students are willing to use Facebook in this way and that there is room to research this further, which it can be added can be of great importance given that much previous research seems to point towards an overall student satisfaction with using Facebook in connection to studies somehow.…”
Section: Introductionmentioning
confidence: 99%
“…αναφ. στο Allen, 2012Donlan, 2012;Van Rooyen, 2015) όσο και στην ελληνική βιβλιογραφία (Δραγογιάννης, Λαλάς & Παπαδοπούλου, 2013· Πετρίδης, 2012), οι έρευνες αφορούν τη χρήση του Facebook ως θεσμικού εργαλείου της τυπικής και ΕξΑΕ, αλλά και ως εργαλείου άτυπης μάθησης (Cain & Policastri, 2011) και σε κάποιες από αυτές εξετάζεται ή διαπιστώνεται η προτίμηση των φοιτητών στο Facebook έναντι των διαδικτυακών εκπαιδευτικών πλατφόρμων (Deng & Tavares, 2013;DiVall & Kirwin, 2012;Schroeder & Greenbowe, 2009, όπ. αναφ στο Manca & Ranieri, 2013.…”
Section: εισαγωγήunclassified
“…Αναφορικά με το study, στους συμμετέχοντες δεν άρεσε, με βάση τα λεγόμενά τους, ο έλεγχος στο περιεχόμενο των αναρτήσεων και η παρακολούθησή τους από τους ακαδημαϊκούς, το οποίο στάθηκε ως αφορμή για να δημιουργηθεί η ΚΟ της ΕΚΠ51 (Donlan, 2012;Rambe & Ng'ambi, 2011;Rutherford, 2013), αλλά και ως ένας χώρος ο οποίος δεν θα επιθυμούσαν να χρησιμοποιηθεί για επικοινωνία με τους καθηγητές τους, θεωρώντας τον ως τον δικό τους χώρο κοινωνικής αλληλεπίδρασης (Donlan, 2012 (Donlan, 2012;Deng & Tavares, 2013;Meishar-Tal et al, 2012;Σωτηριάδου & Παπαδάκης, 2013). Πολύ μεγάλο ρόλο για τη χρήση των ΚΟ φαίνεται να διαδραμάτισε η ευχρηστία του ίδιου του Facebook και εξαιτίας της δημοφιλίας του στους φοιτητές, κάτι που έχει ειπωθεί και σε άλλες έρευνες (Deng & Tavares, 2013;Σωτηριάδου & Παπαδάκης, 2013 …”
Section: λόγοι χρήσης των κλειστών ομάδων του Facebookunclassified
See 2 more Smart Citations